Candidate Gene Analysis for Nitrogen Absorption and Utilization in Japonica Rice at the Seedling Stage Based on a Genome-Wide Association Study - Xin, Wei; Wang, Jingguo; Li, Jia; Zhao, Hongwei; Liu, Hualong; Zheng, Hongliang; Yang, Luomiao; Wang, Chao; Yang, Fan; Chen, Jiahui; Zou, Detang (Frontiers in Plant Science, 2021)
Over-application of nitrogen (N) fertilizer in fields has had a negative impact on both environment and human health. Domesticated rice varieties with high N use efficiency (NUE) reduce fertilizer requirements, enabling sustainable agriculture. Genome-wide association analysis (GWAS) of N absorption and utilization traits under low and high N conditions was performed to obtain 12 quantitative trait locus (QTL) based on genotypic data including 151,202 single-nucleotide polymorphisms (SNPs) developed by re-sequencing 267 japonica rice varieties. Eighteen candidate genes were obtained by integrating GWAS and transcriptome analysis, among them, the functions of OsNRT2.4, OsAMT1.2, and OsAlaAT genes in N transport and assimilation have been identified, OsJAZ12 and OsJAZ13 also play important roles in rice adaptation to abiotic stresses. A NUE-related candidate gene, OsNAC68, was identified by real-time quantative PCR (qRT-PCR) analyses. OsNAC68 encodes a NAC transcription factor and has been shown to be a positive regulator of the drought stress response in rice. Overexpression of OsNAC68 significantly increased rice NUE and grain yield under deficient N conditions, but the difference was not significant under sufficient N conditions. NUE and grain yield significantly decreased under both N supply conditions in the osbnac68 mutant. This study provides crucial insights into the genetic basis of N absorption and utilization in rice, and a NUE-related gene, OsNAC68, was cloned to provide important resources for rice breeding with high NUE and grain yield.